(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Many organizations recommend the use of equations that provide a rapid method of assessing glomerular filtration rate (GFR) to facilitate the detection, evaluation, and management of chronic kidney diseases. Indeed, many clinical laboratories already report estimated GFR (eGFR) values whenever the serum creatinine level is measured. To compare the predictive equations for the measurement of GFR in Bangladeshi population, we measured GFR by creatinine clearance rate (CCR) and also estimated it by Modification of Diet in Renal Disease (MDRD) 4 variables equation and Cockcroft and Gault (C-G) formula in 61 Bangladeshi subjects who were referred to Armed Forces Institute of Pathology, Dhaka Cantonment for the estimation of GFR by physicians during the period of March 2011 to November 2011. Results are expressed as mean ± SD and compared by two-tailed paired t test, Bland-Altman plots for bias, precision (r2), receiver-operating characteristics (ROC) curve, and accuracy within 15%, 30% and 50% of the measured GFR. We included 39 (63.93%) males and 22 (36.06%) females with mean age of 52±14 years. The GFR measured by CCR was 61.30±37.38 mL/min/1.73 m2 and eGFR by MDRD4 and C-G were 51.26±26.86 (P<0.05), 54.98±27.21 (P>0.05) mL/min/1.73 m2 respectively. The bias was 10.55±25.34 mL/min/1.73 m2 for MDRD, 6.32±25.90 mL/min/1.73 m2 for C-G; precision was 0.5407 for MDRD, 0.5201 for C-G; the areas under the ROC curve was 0.5722 (P>0.05) for MDRD4, 0.5444 (P>0.05) for C-G. The percentages of eGFR falling within 15% and 30% of measured GFR were 30%, 52% for MDRD and 35%, 52% for C-G. Both MDRD4 and C-G showed positive bias at GFR<60 mL/min/1.73 m2 and negative bias at GFR >60 mL/min/1.73 m2. The results indicate that Cockcroft-Gault formula is more accurate than MDRD4 equation in the overall GFR range, but MDRD4 appears to be more accurate at GFR <60 mL/min/1.73 m2. J Bangladesh Coll Phys Surg 2015; 33(4): 207-212